2020
DOI: 10.1177/1758835920940939
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the PI3K/Akt/mTOR pathway in estrogen-receptor positive HER2 negative advanced breast cancer

Abstract: Recently many therapeutic classes have emerged in advanced hormone receptor-positive breast cancer, which is the leading cause of cancer death in women. In absence of visceral crisis, treatment relies on endocrine therapy combined with cyclin dependent kinase 4 and 6 inhibitor. Many mechanisms lead to resistance to endocrine therapy, including the activation of intracellular signaling pathways critical for cell survival. Approximately 70% of breast tumors harbor an alteration in the phosphoinositide 3 kinase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 67 publications
0
47
0
2
Order By: Relevance
“…According to the published data, the PI3K/AKT/mTOR pathway is activated in approximately 70% of ovarian or breast cancers [ 88 , 89 ]. For instance, the aberrant activation of the PI3K/AKT/mTOR pathway has been found in 90% of lung adenocarcinomas (ADCs) and 40% of squamous cell carcinomas (SCCs) [ 90 ].…”
Section: Deregulation Of the Pi3k/akt/mtor Pathway In Cancermentioning
confidence: 99%
“…According to the published data, the PI3K/AKT/mTOR pathway is activated in approximately 70% of ovarian or breast cancers [ 88 , 89 ]. For instance, the aberrant activation of the PI3K/AKT/mTOR pathway has been found in 90% of lung adenocarcinomas (ADCs) and 40% of squamous cell carcinomas (SCCs) [ 90 ].…”
Section: Deregulation Of the Pi3k/akt/mtor Pathway In Cancermentioning
confidence: 99%
“…V-ATPase regulates the extracellular environment of tumor cells and the pH of many intracellular compartments, thus enabling tumor cells to maintain a high metabolic rate and contributing to their autophagy, invasion, migration and drug resistance [ 5 , 29 ]. Enhanced phosphoinositide 3-kinase/AKT/mTOR signaling has been associated with BC and found to promote drug resistance [ 30 ]. Everolimus, which inhibits mTORC1 and induces AKT phosphorylation, has been approved for the treatment of postmenopausal women with hormone receptor-positive and human epidermal growth factor receptor 2-negative advanced BC [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Through human proteome microarray, co-IP, immunofluorescence staining and confocal laser microscopy observation, the present study found that QPCT bound to PIK3CA, and PI3K/Akt/mTOR was one of the main intracellular signaling pathways. PI3K signals regulate various cellular functions, including translational regulation of cell proliferation, survival, protein synthesis, glucose metabolism, cell migration and angiogenesis (39)(40)(41)(42)(43). The disruption of this pathway leads to a range of diseases, including cancer (44).…”
Section: Discussionmentioning
confidence: 99%